Detection of Walk Tests in Free-Living Activities Using a Wrist-Worn Device - Sokas, Daivaras; Paliakaitė, Birutė; Rapalis, Andrius; Marozas, Vaidotas; Bailón, Raquel; Petrėnas, Andrius (Frontiers in Physiology, 2021)
Exercise testing to assess the response to physical rehabilitation or lifestyle interventions is administered in clinics thus at best can be repeated only few times a year. This study explores a novel approach to collecting information on functional performance through walk tests, e.g., a 6-min walk test (6MWT), unintentionally performed in free-living activities. Walk tests are detected in step data provided by a wrist-worn device. Only those events of minute-to-minute variation in walking cadence, which are equal or lower than the empirically determined maximal standard deviation (e.g., 5-steps), are considered as walk test candidates. Out of detected walk tests within the non-overlapping sliding time interval (e.g., 1-week), the one with the largest number of steps is chosen as the most representative. This approach is studied on a cohort of 99 subjects, assigned to the groups of patients with cardiovascular disease (CVD) and healthy subjects and over 40 years-old, who were asked to wear the device while maintaining their usual physical activity regimen. The total wear time was 8,864 subject-days after excluding the intervals of occasionally discontinued monitoring. Eighty-two percent (23/28) of CVD patients and 88% (21/24) of healthy subjects over 40 years-old had at least a single 6MWT over the first month of monitoring. Fifty-two percent of CVD patients (12/23) and 91% (19/21) of healthy subjects over 40 years-old exceeded 500m. CVD patients, on average, walked 46m shorter 6MWT distance (p = 0.04) compared to healthy subjects. Unintentional walk testing is feasible and could be valuable for repeated assessment of functional performance outside the clinical setting.